Phylogenetic trees of hemoglobin proteins in notothenioids from the study "Cold-driven hemoglobin evolution in Antarctic notothenioid fishes prior to hemoglobin gene loss in white-blooded icefishes" ... - Desvignes, Thomas; Postlethwait, John (U.S. Antarctic Program (USAP) Data Center, 2023)
All input and output files of the phylogenetic trees of hemoglobin proteins in Notothenioids from the study "Cold-driven hemoglobin evolution in Antarctic notothenioid fishes prior to hemoglobin gene loss in white-blooded icefishes" by Thomas Desvignes, Iliana Bista, Karina Herrera, Audrey Landes, and John H. Postlethwait. ...